Violent Crime Policies in the Teaching and Learning Process in a Criminal Law Perspective - Rohmatullah, Rohmatullah; Arief Fakrulloh, Zudan; Barthos, Megawati (CV. Publikasi Indonesia, 2023)
The reason for viciousness against understudies can happen on the grounds that educators don't grasp the significance of brutality and its unfortunate results. The instructor felt that the understudies would be stopped by whipping. Then again, understudies become angry and defiant to the educator. The conditions and background of acts of violence in education are strung together in a spiral relationship that can appear at any time, by any perpetrator who is involved in an educational institution, as long as there is a trigger for the incident. Recently, there have been various cases that occurred in the educational environment related to violence perpetrated by teachers against their students. Most of the occurrences are caused by the application of disciplinary norms that are too forced on students. Meanwhile, not all students are accustomed to disciplinary behavior. The wrong way of instilling discipline can be in the form of both physical and mental violence against children. The most visible thing is physical violence. It is not uncommon for this to go to court because parents feel they have been disadvantaged.